Manajemen Pengambilan Keputusan Berbasis AHP-SAW dalam Evaluasi Efektivitas Program Makan Bergizi Gratis Pada Anak Usia Sekolah - Maryani, Maryani; Suhartini; Bayu Aditya Syahputra; Aldalia (Direktorat Riset dan Pengabdian kepada Masyarakat Universitas Bina Darma, 2025)
The development of nutrition program implementation has increased the need for systematic evaluation, particularly regarding the free nutritious meal program. Although the program provides substantial benefits, it also presents various evaluation challenges that may affect policy effectiveness. This study aims to analyze the influence of the implementation of the AHP method, the implementation of the SAW method, weight gain evaluation, height gain evaluation, BMI gain evaluation, attendance improvement evaluation, and nutritional intake improvement evaluation on the effectiveness of the free nutritious meal program for school-age children using a Decision Support System based on the Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW). The study population consists of school-age children (6–18 years old) participating in the nutrition program. Sample selection was carried out using purposive sampling with longitudinal data from the National Health and Nutrition Examination Survey (NHANES) 2013–2014, resulting in 2,539 respondents with complete data. The analytical methods used include AHP for determining criteria weights, SAW for scoring program effectiveness, Consistency Ratio analysis for testing AHP matrix consistency, and hypothesis testing using t-test and F-test with IBM SPSS version 26.0 and Python. The results indicate that the AHP matrix demonstrates excellent consistency, with a Consistency Ratio (CR) of 0.0153, suggesting high reliability in expert assessments. The weighted criteria obtained were: weight gain (41.6%), height gain (26.2%), BMI gain (16.1%), attendance improvement (9.9%), and nutritional intake improvement (6.2%). The evaluation results categorized 69.1% of students as “less effective,” 30.0% as “moderately effective,” and only 0.6% as “effective.” Although all indicators showed positive improvements (weight +5.06 kg, height +6.07 cm, BMI +0.42, attendance +12.22%, nutritional intake +311 kcal), the overall program effectiveness still needs improvement. Hypothesis testing shows that all seven independent variables have a significant partial effect on program effectiveness (t-test, p < 0.05), and collectively, the variables significantly affect program effectiveness (F-test = 543.287, p < 0.05). The implications of these findings can serve as a reference for program implementers to enhance nutritional interventions, health monitoring, and evaluation strategies to improve program outcomes for school-age children. Keywords: Program Evaluation, Decision Support System, AHP-SAW, Free Nutritious Meal, Child Health Abstrak Perkembangan implementasi program gizi mendorong meningkatnya kebutuhan evaluasi sistematis, terutama untuk program makan bergizi gratis. Kemudahan yang ditawarkan program ini diiringi dengan berbagai tantangan evaluasi yang dapat memengaruhi efektivitas kebijakan. Penelitian ini bertujuan untuk menganalisis pengaruh implementasi metode AHP, implementasi metode SAW, evaluasi peningkatan berat badan, evaluasi peningkatan tinggi badan, evaluasi peningkatan BMI, evaluasi peningkatan kehadiran, dan evaluasi peningkatan asupan nutrisi terhadap efektivitas program makan bergizi gratis pada anak usia sekolah dengan menggunakan Sistem Pendukung Keputusan berbasis Analytical Hierarchy Process (AHP) dan Simple Additive Weighting (SAW). Populasi dalam penelitian ini adalah anak usia sekolah (6-18 tahun) yang mengikuti program nutrisi. Pemilihan sampel dilakukan menggunakan teknik purposive sampling dengan data longitudinal dari National Health and Nutrition Examination Survey (NHANES) 2013-2014, menghasilkan 2.539 responden dengan data lengkap. Teknik analisis data meliputi AHP untuk pembobotan kriteria, SAW untuk scoring efektivitas, uji konsistensi menggunakan Consistency Ratio, dan pengujian hipotesis menggunakan uji t dan uji F dengan bantuan perangkat lunak IBM SPSS versi 26.0 dan pemrograman Python. Hasil studi ini menunjukkan matriks AHP mencapai konsistensi excellent dengan Consistency Ratio (CR) sebesar 0.0153, mengindikasikan keandalan tinggi dalam expert judgment. Bobot kriteria yang diperoleh adalah: peningkatan berat badan (41.6%), peningkatan tinggi badan (26.2%), peningkatan BMI (16.1%), peningkatan kehadiran (9.9%), dan peningkatan asupan nutrisi (6.2%). Hasil evaluasi menunjukkan 69.1% siswa berkategori